Controlling of jerk chaotic system via linear feedback control strategies - Karam Adel Abed (Institute of Advanced Engineering and Science, 2020)
In this paper, the strategies of linear feedback control for jerk system is considered. These strategies consist of four strategies (ordinary feedback control, dislocated feedback control, speed feedback control, and enhancing feedback control). We propose to combine between these strategies and obtained a better result from this combine. Numerical solution achieved the same results.